2000
DOI: 10.1212/wnl.54.4.833
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous estrogen levels and Alzheimer’s disease among postmenopausal women

Abstract: The results of this preliminary case-control study suggest that estradiol levels may decline significantly in women in whom AD develops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(139 citation statements)
references
References 42 publications
5
127
1
6
Order By: Relevance
“…Some studies have not shown significant differences between healthy women and women with AD (Cunningham et al, 2001). On the contrary, other studies have found decreased levels of estradiol in AD patients (Manly et al, 2000). One study has reported decreased estradiol levels in the cerebrospinal fluid of AD patients and a negative correlation with ␤-amyloid levels (Schonknecht et al, 2001).…”
Section: Steroidal Aging In Humansmentioning
confidence: 93%
“…Some studies have not shown significant differences between healthy women and women with AD (Cunningham et al, 2001). On the contrary, other studies have found decreased levels of estradiol in AD patients (Manly et al, 2000). One study has reported decreased estradiol levels in the cerebrospinal fluid of AD patients and a negative correlation with ␤-amyloid levels (Schonknecht et al, 2001).…”
Section: Steroidal Aging In Humansmentioning
confidence: 93%
“…In fact, it is long known that women experience a sharp increase in the risk of developing AD after menopause [65,103]. This is further strengthened by the fact that ovariectomy promotes the amyloidogenic processing of APP [76,122,166,175], and that these effects are partially or totally reverted by estrogen treatment [122,175].…”
Section: Igf1-r Neurotrophin Signaling and Ad: A Tale Of Receptors mentioning
confidence: 99%
“…Relatively low estradiol levels in the late postmenopause have been linked to Alzheimer's disease risk in women (Manly et al, 2000;Hoskin et al, 2004), but again there are inconsistencies (Geerlings et al, 2003).…”
Section: Introductionmentioning
confidence: 99%